THE ROLE OF, AND DISCLOSURE, GOVERNANCE TRANSPARENCY IN ACTIVATING THE IMPLEMENTATION OF PROGRAM AND PERFORMANCE BUDGETING, AS AN ALTERNATIVE TO ITEM BALANCING (World Economics and Finance Bulletin, 2025)
This study aims to achieve integration between the principles of governance and the adoption of the application of program and performance budgeting, to achieve the application of the accrual basis, as an alternative to the adoption of the application of the classic item budget that embraces the cash basis, which is considered the cornerstone for encouraging chaos and corruption. To arrive at the results, the field study relied on 70 questionnaires distributed to the study sample, which included academics interested in government accounting, system users working in government accounting units, and representatives of the Ministry of Finance. The study concluded that the integration between the principles of public sector governance and the dimensions of the program and performance budget, represented by (application of the accrual basis, development of the characteristics of the quality of government financial statements), has a significant and positive impact on the effectiveness of planning and control, eliminating corruption, and achieving the element of equality in the distribution of financial allocations in the general budget .
Keywords: principles of governance; program and performance budgeting